Análisis termodinámico de microencapsulados con diferentes biopolímeros obtenidos por secado por aspersión para establecer las condiciones de máxima estabilidad durante su almacenamiento - Bonilla Zavaleta, Enrique (Universidad Autónoma Metropolitana, 2010)
An effective way for protecting foods against spoilage mechanisms is to reduce their water content during processing. Thus, the food manufacturers of dried foods are continually trying to establish the most suitable conditions under which these products can be distributed, handled and/or stored, in order to minimize deleterious physical and/or chemical changes. Spray drying is a technique employed for encapsulating active compounds such as flavorings and volatiles in biopolymeric matrices, in order to protect them, reduce their evaporation, provide an easier handling, and control their release during storage and upon application. Water activity (aw) and glass transition temperature (Tg) have been extensively used for predicting the shelf-life of foods, but lately have been attributed with a limited prediction capability. Thus, a new point of view has been proposed for viewing the problem of dried foods stability. The thermodynamics of water vapor adsorption may constitute a reliable scientific criterion for predicting the stability under storage conditions and shelf-life of dry foods. The objective of this work was to encapsulate canola oil in three different biopolymer matrices (whey protein concentrate (WPC), soybean protein isolate (SPI), and mesquite gum (MG)) using the spray drying technique, and to evaluate the water vapor sorption process of the microcapsules by determining the differential and integral thermodynamic properties, and using them for predicting the most suitable storage conditions (water activity and temperature), by calculating the minimum integral entropy of the water vapor molecules adsorbed on the microcapsules surfaces. Initially, a thermal analysis of the biopolymers was conducted at 40, 60, and 80 °C, in order to obtain and evaluate the moisture diffusion coefficient and the activation energy (AE) required by each one of the biopolymers during an isothermal drying process. AE was used as a criterion for selecting the most suitable biopolymers as wall materials for microencapsulation. The results showed that SPI exhibited the highest AE, followed by MG, and by WPC, respectively. Thus, SPI was considered as the best material for microencapsulating lipids by spray drying and protecting them against oxidation. Afterwards, canola oil-in-water emulsions were prepared with these biopolymers and spray dried. The microcapsules were exposed to saturated solutions of different salts at 15, 25, and 35 °C until they achieved constant aw in the interval of 0.12-0.89. The adsorption isotherms were subjected to a thermodynamic analysis calculating the differential and integral enthalpy and entropy, as well as Gibbs free energy. The changes undergone by the microcapsules were analyzed using these parameters. The point or zone of maximum stability determined using this methodology was compared with the moisture values of the monolayer obtained using the Guggenheim-Anderson-de Boer (GAB) equation. The minimum integral entropy of the microcapsules maintained at 25 °C occurred at 10.40 g of water per 100 g of dry solids (aw of 0.55) for MG, 10.59 g of water per 100 g of dry solids (aw of 0.68) for SPI, and 6.38 g of water per 100 g of dry solids (aw of 0.46) for WPC. The integral enthalpy-entropy compensation indicated that the water vapor adsorption was controlled by entropic mechanisms at low aw values, but by enthalpic mechanisms at high aw values. Likewise, the microcapsules were subjected to a dynamic water vapor adsorption at 25 °C, in order to evaluate the water vapor adsorption constants, and for determining the aw value or relative humidity where pore blockage occurs. This blockage occurred when the water vapor adsorption took place at relative humidities of 64.3, 52.9, and 43.2 % (aw values of 0.643, 0529, and 0.432), for SPI, MG, and WPC, respectively. These results confirmed the results obtained with the minimum integral entropy, the enthalpy- entropy compensation, and the micropores volume.; Una forma efectiva de proteger los alimentos contra los mecanismos de deterioro es reducir su contenido de agua durante su procesamiento. Por lo tanto, los productores de alimentos deshidratados están continuamente tratando de establecer las condiciones más adecuadas bajo las cuales estos productos pueden ser distribuidos, manipulados y/o almacenados para evitar o minimizar cambios físicos y/o químicos nocivos. El secado por aspersión es una técnica para llevar a cabo la encapsulación de compuestos activos sensibles, tales como volátiles y sabores, en acarreadores sólidos para incrementar su protección, reducir la evaporación, promover un manejo más fácil, y controlar su liberación durante el almacenamiento y aplicación. La actividad de agua (aw) y la temperatura de transición vítrea (Tg) se han utilizado extensamente para predecir la vida de anaquel de los alimentos, sin embargo, estas teorías presentan limitaciones. Por lo tanto, el problema de la estabilidad de los alimentos puede ser abordado a partir de un nuevo punto de vista. La termodinámica de la adsorción de vapor de agua podría proponer un confiable criterio científico para predecir la estabilidad en el almacenamiento y la vida de anaquel de los alimentos deshidratados. Por lo tanto, el objetivo de este trabajo fue microencapsular aceite de canola en diferentes materiales de pared (concentrado de proteína de suero de leche (CPS), aislado de proteína de soya (APS) y goma de mezquite(GM)) usando la técnica de secado por aspersión para evaluar el proceso de adsorción de las microcápsulas de aceite de canola usando propiedades diferenciales e integrales y así predecir las condiciones de almacenamiento más adecuadas (actividad de agua y temperatura) calculando el valor de la mínima entropía integral de las moléculas de vapor de agua adsorbidas sobre la superficie de las microcápsulas. Los resultados mostraron que el APS presentó las mayores energías, seguido por la GM y el CPS, respectivamente; por lo que el APS puede ser considerado como el más conveniente de los materiales de pared para proveer protección contra la oxidación a los lípidos encapsulados por secado por aspersión. Posteriormente, se prepararon emulsiones con estos biopolímeros y se sometieron a secado por aspersión. Las microcápsulas de aceite de canola fueron almacenadas en soluciones saturadas de diferentes sales que proveyeron microclimas en el intervalo de aw de 0.12 a 0.89 y mantenidas a 15, 25 y 35 °C hasta su equilibrio. A partir de las isotermas de adsorción se realizó un análisis termodinámico calculando propiedades termodinámicas (entalpía y entropía) diferenciales e integrales, así como la energía libre de Gibbs, con las cuales fueron analizados los cambios que sufren estos materiales durante el proceso de adsorción. El punto o zona de máxima estabilidad obtenida con esta metodología fue comparada con los valores de humedad en la monocapa obtenidos a través de la ecuación de Guggenheim-Anderson-de Boer (GAB). El punto de mínima entropía integral de las microcápsulas mantenidas a 25 °C ocurrió a 10.40 g agua por 100 g de sólidos secos (aw de 0.55) para GM, 10.59 g agua por 100 g de sólidos secos (aw de 0.68) para APS, y 6.38 g agua por 100 g de sólidos secos (aw de 0.46) para CPS. La compensación entalpía-entropía integral indicó que la adsorción de vapor de agua fue controlada por mecanismos entrópicos a bajas aw, pero por mecanismos entálpicos a altas aw. Asimismo, se realizó la adsorción dinámica de vapor de agua sobre las microcápsulas a 25 °C con el objetivo de evaluar las constantes de adsorción de vapor de agua y determinar la aw o humedad relativa en donde se presenta el bloqueo de poro. Este bloqueo ocurrió cuando la adsorción de vapor de agua se realizó en un ambiente con humedades relativas de 64.3, 52.9 y 43.2 % (aw = 0.643. 0.529 y 0.432 para APS, GM y CPS, respectivamente), confirmando los resultados termodinámicos obtenidos con la mínima entropía integral, la compensación entalpía-entropía y el volumen de microporos.